EVALUASI PENERAPAN KEBIJAKAN SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU (PPDB) DI SMA NEGERI 2 BANDUNG - Aulia Nindyta Pratiwi, - (2020)
Admission of new students to the zoning system has been put in place in Indonesia from 2017 through Permendikbud no. 17 of 2017 which applies to all municipal and district education offices in Indonesia. The purpose of the zoning system is to equalize access to education, but in its implementation in the field there are a number of schools that still need to adapt to the impact of the implementation of this zoning system. One of them is in SMA Negeri 2 Bandung, which was the first cluster school before the zoning system was accepted by new students. Therefore this study aims to determine the description of the adoption of the New Student Admission Policy zoning system in SMA Negeri 2 Bandung. The research method used in this study is a descriptive research method with a qualitative approach. Data collection techniques through interviews, observation and documentation study. Data validity checking is done by triangulation of sources and techniques. Data analysis techniques used are using the William N Dunn model public policy analysis technique with the CIPP (Context, Input, Process, Product) approach which explains that the advantages of implementing a zoning system on Student Admissions New in SMA Negeri 2 Bandung The results showed that the application of the zoning system on the acceptance of New Students in SMA Negeri 2 Bandung has been going very well but the school is still adapting to the impact of implementing the zoning system policies including Improving the quality of learning, Specialization of Students which has an impact on the division of study groups, characteristics of participants students to the learning process in class. This is what still creates shortcomings in the implementation of the zoning system in SMA Negeri 2 Bandung.. Keywords : Zoning System Policy, Equal Access to Education, SMA Negeri 2 Bandung.